Anticounterfeiting Materials: Patterned and Iridescent Plastics with 3D Inverse Opal Structure for Anticounterfeiting of the Banknotes (Advanced Optical Materials 8/2018). Issue 8 (18th April 2018) - Meng, Yao; Liu, Fangfang; Umair, Malik Muhammad; Ju, Benzhi; Zhang, Shufen; Tang, Bingtao
Abstract : Polyvinylidene fluoride (PVDF) structural color films with 3D inverse opal structure have been prepared by Bingtao Tang and co‐workers (article number1701351 ). The iridescent plastic films show excellent durability and can be patterned easily. The patterns exhibit six distinct color states when the viewing angles increased from 5° to 45° due to the strong angle‐dependency effect which makes the film a higher security anti‐counterfeiting material.